A method for preparing anisaldehyde by oxygen vacancy-induced water-based electrocatalytic selective oxidation of benzyl C-H bond
By introducing oxygen vacancy structures into cobalt oxide catalysts, the problem of benzyl C(sp3)–H bond activation in aqueous electrochemistry was solved, achieving highly selective and high Faradaic efficiency preparation of anisaldehyde. The reaction conditions are mild and suitable for the selective oxidation of a variety of methyl aromatic compounds.
Patent Information
- Application Number
- CN202610701377.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-03-05
- Filing Date
- 2026-05-20
- Publication Date
- 2026-06-26
AI Technical Summary
In the prior art, cobalt-based oxides are difficult to effectively activate benzyl C(sp3)–H bonds under aqueous electrochemical conditions. The reaction conditions are harsh, the selectivity is poor, the over-oxidation is serious, the Faraday efficiency is low, and it depends on strong oxidants or organic solvents.
By introducing a controllable oxygen vacancy structure into a cobalt oxide catalyst, and using cobalt tetroxide (Co3O4) containing oxygen vacancies as an anode, electrochemical oxidation is carried out in an aqueous electrolyte to generate anisaldehyde products, thereby inhibiting the oxygen evolution reaction and improving the active oxygen supply capacity of the catalyst surface.
It achieves highly selective and high Faradaic efficiency oxidation of benzyl C(sp3)–H bonds in a mild aqueous electrolyte to generate anisaldehyde, avoiding the use of high temperature, high pressure or strong oxidants, improving product selectivity and Faradaic efficiency, and is environmentally friendly with a wide range of applicable substrates.
Smart Images

Figure CN122279626A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic electrocatalysis technology, specifically relating to an oxygen vacancy-induced aqueous electrocatalytic benzyl C(sp) group. 3 A method for preparing anisaldehyde by selective oxidation of the )-H bond. Background Technology
[0002] Cobalt-based oxides have multiple tunable valence states (Co) 2+ / Co 3+ / Co 4+ Cobalt oxides, with their characteristics of generating highly reactive oxygen species, are considered potential electrocatalytic oxidation materials. However, existing studies have shown that conventional cobalt-based oxides are difficult to effectively activate benzyl C(sp) under aqueous electrochemical conditions. 3 The cobalt-based material exhibits a high degree of catalytic activity (C₂-H) bonding, and its true active phase and reaction mechanism remain unclear. Especially under high potential conditions, cobalt-based materials are prone to complex surface reconstruction and phase transitions, which can affect catalytic activity and increase the difficulty of reaction regulation. Benzyl C(sp) 3 The oxidation of methyl aromatic compounds to anisaldehyde is hampered by harsh reaction conditions, poor selectivity, severe over-oxidation, low Faraday efficiency, and reliance on strong oxidants or organic solvents.
[0003] Therefore, how to suppress the oxygen evolution reaction and reduce the benzyl C(sp) content in an aqueous electrochemical system is crucial. 3 Breaking down the activation barrier of the H-H bond and achieving highly selective and high Faradaic efficiency in the preparation of anisaldehyde has become a key technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] To address the problems in existing technologies regarding the oxidation of methyl aromatic compounds to anisaldehyde, such as harsh reaction conditions, poor selectivity, severe over-oxidation, low Faraday efficiency, and dependence of the reaction system on strong oxidants or organic solvents, the present invention aims to provide an oxygen vacancy-induced aqueous electrocatalytic method for benzyl C(sp...) 3 A method for selectively oxidizing β-H bonds to prepare anisaldehyde significantly improves the electrophilicity and active oxygen supply capacity of oxygen species on the catalyst surface by introducing a controllable oxygen vacancy structure into cobalt-based metal oxides, thereby achieving the preparation of benzyl C(sp)-H bonds under aqueous electrolysis conditions. 3 The efficient and selective activation and oxidation of the )–H bond leads to the highly selective generation of the corresponding anisaldehyde product at a lower potential, thus inhibiting the deep oxidation of methyl aromatic compounds to carboxylic acids.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] This invention provides a method for the selective oxidation of benzyl CH bonds in an aqueous system induced by oxygen vacancy to prepare anisaldehyde. In the electrochemical reaction system, a transition metal oxide containing oxygen vacancies is used as the anode, and under the action of an external electric field, a methyl aromatic compound undergoes an electrochemical oxidation reaction to generate anisaldehyde.
[0007] In a preferred embodiment, the method includes the following steps:
[0008] S1. Construct an electrochemical reaction system, the electrochemical reaction system including an anode, a cathode and an electrolyte; load a cobalt oxide catalyst on the anode;
[0009] S2. Introduce a methyl aromatic compound containing a benzyl CH bond into the electrochemical reaction system;
[0010] S3. An electrolytic reaction is carried out under an external tank pressure to cause the methyl aromatic compound to undergo a selective oxidation reaction at the anode, generating the corresponding anisaldehyde product.
[0011] Furthermore, in step S1, the cobalt oxide catalyst is cobalt tetroxide (Co3O4) containing oxygen vacancies.
[0012] Oxygen-containing vacancies are introduced through inert atmosphere heat treatment. These vacancies are used to regulate the transition metal-oxygen bond structure and enhance the ability of active oxygen species to form on the catalyst surface.
[0013] Furthermore, the oxygen-vacant cobalt tetroxide is prepared by the following method:
[0014] First, a cobalt hydroxide precursor is electrodeposited on the surface of a conductive substrate, and then calcined under an inert atmosphere at a temperature of 400-600 °C for 1-4 h.
[0015] Furthermore, the cobalt oxide catalyst is supported on a conductive substrate, which is either a titanium mesh or a titanium foil, wherein the titanium mesh is 100-600 mesh.
[0016] Furthermore, in step S1, the cathode is an inert electrode.
[0017] Furthermore, in step S1, the electrochemical reaction is carried out in a dual-electrode system without a diaphragm or with an ion-exchange membrane.
[0018] Furthermore, in step S1, the electrolyte is an electrolyte system mainly composed of water, and may optionally contain a small amount of organic co-solvent, which is one or more of acetonitrile, methanol or acetic acid.
[0019] Furthermore, the electrolyte system is a weakly alkaline, neutral, or neutral-to-acidic electrolyte.
[0020] Furthermore, the methyl aromatic compound is toluene and its substituted derivatives; wherein the substituent is a halogen, alkyl, alkoxy, nitro or a combination thereof.
[0021] Furthermore, in step S3, the electrolysis reaction is carried out under normal temperature and pressure conditions.
[0022] Furthermore, in step S3, the applied tank voltage is a potential range capable of driving the selective oxidation of methyl aromatic compounds and inhibiting the oxygen evolution reaction, and the applied tank voltage is 2.5~3.0 V.
[0023] This invention uses an oxygen-vacancy-containing cobalt oxide electrocatalyst supported on a conductive substrate as the anode catalyst layer, and achieves the synthesis of methyl aromatic C(sp) in a mild aqueous electrolyte under the drive of an external electric field. 3 This method involves the efficient and selective oxidation of the )–H bond to generate the corresponding anisaldehyde products. The reaction conditions are mild, requiring no high temperature, high pressure, or chemical oxidants, significantly inhibiting the over-oxidation of anisaldehyde and improving product selectivity and Faraday efficiency. The catalyst used is prepared by electrodeposition and high-temperature inert atmosphere calcination, exhibiting stable structure and suitability for the selective oxidation of various methyl aromatic compounds. This technology is environmentally friendly, simple to operate, and has promising prospects for industrial application.
[0024] Beneficial technical effects of the present invention:
[0025] 1. Mild reaction conditions: This invention uses an aqueous electrochemical system for the reaction, avoiding the high temperature and high pressure reaction conditions or the need for strong oxidants commonly found in the traditional synthesis of anisaldehyde, which greatly reduces energy consumption and equipment requirements, and improves process safety and ease of operation.
[0026] 2. High Selectivity and Faraday Efficiency: Through precise electronic structure regulation of the oxygen-vacancy-containing cobalt oxide catalyst, the excessive oxidation of anisaldehyde to byproducts such as carboxylic acids is effectively suppressed, significantly improving the yield and selectivity of the target anisaldehyde. Simultaneously, oxygen vacancies enhance the electron transfer capability of the catalyst surface active sites, improving Faraday efficiency and achieving efficient utilization of electrical energy.
[0027] 3. Green, environmentally friendly, and sustainable: The method of this invention does not require the addition of additional organic solvents or chemical oxidants, reducing the emission of harmful substances and environmental pollution. It conforms to the concept of green chemistry, is suitable for large-scale industrial promotion and application, and helps to achieve green manufacturing and sustainable development goals.
[0028] 4. Wide range of applicable substrates: The catalyst and process of this invention show good applicability to a variety of methyl aromatic compounds and their substituted derivatives, and have strong universality and flexibility, which can meet the synthesis needs of different anisaldehyde products and expand their application prospects.
[0029] 5. The catalyst is easy to prepare and the process is easy to scale up: The catalyst is prepared by conventional processes such as electrodeposition and high-temperature calcination. The process is simple and easy to control. The catalyst has a stable structure and good reusability. The equipment is simple in structure, easy to operate, and easy to achieve continuous production, which is conducive to industrial application, reduces production costs, and improves economic benefits.
[0030] Instruction manual illustrations
[0031] Figure 1 The graph shows a comparison of the conversion rate of p-methoxytoluene and the Faraday efficiency and selectivity of p-methoxybenzaldehyde for the catalysts obtained in Example 1 and Comparative Example 1.
[0032] Figure 2 The XRD pattern of the Co3O4 catalyst obtained in Comparative Example 1 is shown.
[0033] Figure 3 The XRD pattern of the Vo-Co3O4 catalyst obtained in Example 1;
[0034] Figure 4 The image shows a SEM image of the Co3O4 catalyst obtained in Comparative Example 1.
[0035] Figure 5 The image shows a SEM image of the Vo-Co3O4 catalyst obtained in Example 1.
[0036] Figure 6 The image shows a TEM image of the Co3O4 catalyst obtained in Comparative Example 1.
[0037] Figure 7 TEM image of the Vo-Co3O4 catalyst obtained in Example 1;
[0038] Figure 8 The EPR diagram of the Co3O4 catalyst obtained in Comparative Example 1 is shown.
[0039] Figure 9 The EPR spectrum of the Vo-Co3O4 catalyst obtained in Example 1 is shown below.
[0040] Figure 10 XPS 1s plot of the Co3O4 catalyst obtained in Comparative Example 1;
[0041] Figure 11 The image shows the XPS 1s plot of the Vo-Co3O4 catalyst obtained in Example 1. Detailed Implementation
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0043] The present invention will be further described below with reference to specific embodiments and accompanying drawings:
[0044] Example 1
[0045] I. Catalyst Preparation:
[0046] (1) Pretreatment of titanium mesh substrate;
[0047] The titanium mesh was cut into sheet electrodes with a size of 1 cm × 2 cm, and the mesh size was 300 mesh. First, the titanium mesh was immersed in acetone for 15 min to remove surface oil and organic impurities; then it was transferred to a solution with a concentration of 3 mol·L⁻¹. -1 The titanium mesh was chemically etched in a hydrochloric acid solution for 15 minutes to remove the surface oxide layer. After etching, the titanium mesh was repeatedly rinsed with deionized water until the washing solution was neutral. The treated titanium mesh was then vacuum dried at room temperature and placed in a desiccator for later use.
[0048] (2) Electrodeposition of Co(OH)2 precursor;
[0049] Electrodeposition was performed on an electrochemical workstation using a three-electrode system. A 10 mM aqueous solution of cobalt nitrate (Co(NO3)2) was used as the electrolyte. A pretreated titanium mesh (effective deposition area of 1 cm × 1 cm) was used as the working electrode, a platinum mesh (1 cm × 1 cm) was used as the counter electrode, and a saturated calomel electrode (SCE) was used as the reference electrode.
[0050] Electrodeposition was performed at -1.0 V (relative to SCE) under constant potential conditions for 10 min. After deposition, the working electrode was removed, thoroughly rinsed with deionized water to remove residual electrolyte, and dried overnight in an oven at 60 °C to obtain the Co(OH)2 precursor loaded on a titanium mesh.
[0051] (3) Preparation of oxygen-containing vacancy Co3O4;
[0052] The above Co(OH)2 precursor was placed in a tube furnace and heated at 5 °C·min under an argon atmosphere. -1 The temperature was increased to 500 °C at a certain rate and held at that temperature for 2 h.
[0053] A Co3O4 electrocatalyst containing oxygen vacancies (denoted as Vo-Co3O4 / Ti network) was obtained. After calcination, the sample was naturally cooled to room temperature in the corresponding atmosphere.
[0054] II. The conduct of electrochemical oxidation reactions in aqueous systems:
[0055] Electrochemical oxidation was carried out in a diaphragm-free two-electrode system under constant voltage (at ambient temperature and pressure). The electrolyte in the electrolytic cell had a volume of 15 mL and was a mixed solution of 0.1 M K2SO4 and acetonitrile (volume ratio 7:3). The concentration of the substrate p-methoxytoluene was 10 mmol / L.
[0056] An electrolytic reaction was carried out at room temperature and atmospheric pressure using a Vo-Co3O4Ti mesh (effective area of 1 cm × 1 cm) as the anode and a carbon rod with a diameter of 6 mm as the cathode, with a constant cell voltage of 2.85 V applied.
[0057] III. Product Identification and Quantitative Analysis:
[0058] After the electrolysis reaction was completed, the reaction system was cooled to room temperature, and an appropriate amount of ethyl acetate was added to the reaction solution for extraction. After thorough shaking, the mixture was separated, and the organic phase was collected. The obtained extract was used for qualitative and quantitative analysis of the reaction products.
[0059] Qualitative analysis of the reaction products was performed using gas chromatography-mass spectrometry (GC-MS), and the chemical structures of the anisaldehyde products were confirmed by comparison with a standard spectral library. Quantitative analysis was performed using gas chromatography, and a calibration curve was established using standards of the target products. The content of the reaction products was then quantitatively calculated using the external standard method.
[0060] Example 2
[0061] I. Catalyst Preparation:
[0062] (1) Pretreatment of titanium mesh substrate;
[0063] The titanium mesh was cut into sheet electrodes with a size of 1 cm × 2 cm, and the mesh size was 300 mesh. First, the titanium mesh was immersed in acetone for 15 min to remove surface oil and organic impurities; then it was transferred to a solution with a concentration of 3 mol·L⁻¹. -1 The titanium mesh was chemically etched in a hydrochloric acid solution for 15 minutes to remove the surface oxide layer. After etching, the titanium mesh was repeatedly rinsed with deionized water until the washing solution was neutral. The treated titanium mesh was then vacuum dried at room temperature and placed in a desiccator for later use.
[0064] (2) Electrodeposition of Co(OH)2 precursor;
[0065] Electrodeposition was performed on an electrochemical workstation using a three-electrode system. A 10 mM aqueous solution of cobalt nitrate (Co(NO3)2) was used as the electrolyte. A pretreated titanium mesh (effective deposition area of 1 cm × 1 cm) was used as the working electrode, a platinum mesh (1 cm × 1 cm) was used as the counter electrode, and a saturated calomel electrode (SCE) was used as the reference electrode.
[0066] Electrodeposition was performed at -1.0 V (relative to SCE) under constant potential conditions for 10 min. After deposition, the working electrode was removed, thoroughly rinsed with deionized water to remove residual electrolyte, and dried overnight in an oven at 60 °C to obtain the Co(OH)2 precursor loaded on a titanium mesh.
[0067] (3) Preparation of oxygen-containing vacancy Co3O4;
[0068] The above Co(OH)2 precursor was placed in a tube furnace and heated at 5 °C·min under an argon atmosphere. -1 The temperature was increased to 400 °C at a certain rate and held at that temperature for 4 h.
[0069] A Co3O4 electrocatalyst containing oxygen vacancies (denoted as Vo-Co3O4 / Ti network) was obtained. After calcination, the sample was naturally cooled to room temperature in the corresponding atmosphere.
[0070] II. The conduct of electrochemical oxidation reactions in aqueous systems:
[0071] Electrochemical oxidation was carried out in a diaphragm-free two-electrode system under constant voltage (at ambient temperature and pressure). The electrolyte in the electrolytic cell had a volume of 15 mL and was a mixed solution of 0.1 M K2SO4 and acetonitrile (volume ratio 7:3). The concentration of the substrate p-methoxytoluene was 10 mmol / L.
[0072] An electrolytic reaction was carried out at room temperature and atmospheric pressure using a Vo-Co3O4 / Ti mesh (effective area of 1 cm × 1 cm) as the anode and a carbon rod with a diameter of 6 mm as the cathode, with a constant cell voltage of 3.0 V applied.
[0073] III. Product Identification and Quantitative Analysis:
[0074] After the electrolysis reaction was completed, the reaction system was cooled to room temperature, and an appropriate amount of ethyl acetate was added to the reaction solution for extraction. After thorough shaking, the mixture was separated, and the organic phase was collected. The obtained extract was used for qualitative and quantitative analysis of the reaction products.
[0075] Qualitative analysis of the reaction products was performed using gas chromatography-mass spectrometry (GC-MS), and the chemical structures of the anisaldehyde products were confirmed by comparison with a standard spectral library. Quantitative analysis was performed using gas chromatography, and a calibration curve was established using standards of the target products. The content of the reaction products was then quantitatively calculated using the external standard method.
[0076] Example 3
[0077] I. Catalyst Preparation:
[0078] (1) Pretreatment of titanium mesh substrate;
[0079] The titanium mesh was cut into sheet electrodes with a size of 1 cm × 2 cm, and the mesh size was 300 mesh. First, the titanium mesh was immersed in acetone for 15 min to remove surface oil and organic impurities; then it was transferred to a solution with a concentration of 3 mol·L⁻¹. -1 The titanium mesh was chemically etched in a hydrochloric acid solution for 15 minutes to remove the surface oxide layer. After etching, the titanium mesh was repeatedly rinsed with deionized water until the washing solution was neutral. The treated titanium mesh was then vacuum dried at room temperature and placed in a desiccator for later use.
[0080] (2) Electrodeposition of Co(OH)2 precursor;
[0081] Electrodeposition was performed on an electrochemical workstation using a three-electrode system. A 10 mM aqueous solution of cobalt nitrate (Co(NO3)2) was used as the electrolyte. A pretreated titanium mesh (effective deposition area of 1 cm × 1 cm) was used as the working electrode, a platinum mesh (1 cm × 1 cm) was used as the counter electrode, and a saturated calomel electrode (SCE) was used as the reference electrode.
[0082] Electrodeposition was performed at -1.0 V (relative to SCE) under constant potential conditions for 10 min. After deposition, the working electrode was removed, thoroughly rinsed with deionized water to remove residual electrolyte, and dried overnight in an oven at 60 °C to obtain the Co(OH)2 precursor loaded on a titanium mesh.
[0083] (3) Preparation of oxygen-containing vacancy Co3O4;
[0084] The above Co(OH)2 precursor was placed in a tube furnace and heated at 5 °C·min under an argon atmosphere. -1 The temperature was increased to 600 °C at a certain rate and held at that temperature for 1 h.
[0085] A Co3O4 electrocatalyst containing oxygen vacancies (denoted as Vo-Co3O4 / Ti network) was obtained. After calcination, the sample was naturally cooled to room temperature in the corresponding atmosphere.
[0086] II. The conduct of electrochemical oxidation reactions in aqueous systems:
[0087] Electrochemical oxidation was carried out in a diaphragm-free two-electrode system under constant voltage (at ambient temperature and pressure). The electrolyte in the electrolytic cell had a volume of 15 mL and was a mixed solution of 0.1 M K2SO4 and acetonitrile (volume ratio 7:3). The concentration of the substrate p-methoxytoluene was 10 mmol / L.
[0088] An electrolytic reaction was carried out at room temperature and atmospheric pressure using a Vo-Co3O4 / Ti mesh (effective area of 1 cm × 1 cm) as the anode and a carbon rod with a diameter of 6 mm as the cathode, with a constant cell voltage of 2.5 V applied.
[0089] III. Product Identification and Quantitative Analysis:
[0090] After the electrolysis reaction was completed, the reaction system was cooled to room temperature, and an appropriate amount of ethyl acetate was added to the reaction solution for extraction. After thorough shaking, the mixture was separated, and the organic phase was collected. The obtained extract was used for qualitative and quantitative analysis of the reaction products.
[0091] Qualitative analysis of the reaction products was performed using gas chromatography-mass spectrometry (GC-MS), and the chemical structures of the anisaldehyde products were confirmed by comparison with a standard spectral library. Quantitative analysis was performed using gas chromatography, and a calibration curve was established using standards of the target products. The content of the reaction products was then quantitatively calculated using the external standard method.
[0092] Comparative Example 1
[0093] I. Catalyst Preparation:
[0094] (1) Pretreatment of titanium mesh substrate;
[0095] The titanium mesh was cut into sheet electrodes with a size of 1 cm × 2 cm, and the mesh size was 300 mesh. First, the titanium mesh was immersed in acetone for 15 min to remove surface oil and organic impurities; then it was transferred to a solution with a concentration of 3 mol·L⁻¹. -1 The titanium mesh was chemically etched in a hydrochloric acid solution for 15 minutes to remove the surface oxide layer. After etching, the titanium mesh was repeatedly rinsed with deionized water until the washing solution was neutral. The treated titanium mesh was then vacuum dried at room temperature and placed in a desiccator for later use.
[0096] (2) Electrodeposition of Co(OH)2 precursor;
[0097] Electrodeposition was performed on an electrochemical workstation using a three-electrode system. A 10 mM aqueous solution of cobalt nitrate (Co(NO3)2) was used as the electrolyte. A pretreated titanium mesh (effective deposition area of 1 cm × 1 cm) was used as the working electrode, a platinum mesh (1 cm × 1 cm) was used as the counter electrode, and a saturated calomel electrode (SCE) was used as the reference electrode.
[0098] Electrodeposition was performed at -1.0 V (relative to SCE) under constant potential conditions for 10 min. After deposition, the working electrode was removed, thoroughly rinsed with deionized water to remove residual electrolyte, and dried overnight in an oven at 60 °C to obtain the Co(OH)2 precursor loaded on a titanium mesh.
[0099] (3) Preparation of Co3O4;
[0100] The above-mentioned Co(OH)2 precursor was placed in a tube furnace and heated at 5 °C·min in an air atmosphere. -1 The temperature was increased to 500 °C at a certain rate and held at that temperature for 2 h.
[0101] A Co3O4 electrocatalyst (denoted as Co3O4 / Ti mesh) was obtained. After calcination, the sample was naturally cooled to room temperature in the corresponding atmosphere.
[0102] II. The conduct of electrochemical oxidation reactions in aqueous systems:
[0103] Electrochemical oxidation was carried out in a diaphragm-free two-electrode system under constant voltage (at ambient temperature and pressure). The electrolyte in the electrolytic cell had a volume of 15 mL and was a mixed solution of 0.1 M K2SO4 and acetonitrile (volume ratio 7:3). The concentration of the substrate p-methoxytoluene was 10 mmol / L.
[0104] An electrolytic reaction was carried out at room temperature and atmospheric pressure using a Co3O4 / Ti mesh (effective area of 1 cm × 1 cm) as the anode and a carbon rod with a diameter of 6 mm as the cathode, with a constant cell voltage of 2.85 V applied.
[0105] III. Product Identification and Quantitative Analysis:
[0106] After the electrolysis reaction was completed, the reaction system was cooled to room temperature, and an appropriate amount of ethyl acetate was added to the reaction solution for extraction. After thorough shaking, the mixture was separated, and the organic phase was collected. The obtained extract was used for qualitative and quantitative analysis of the reaction products.
[0107] Qualitative analysis of the reaction products was performed using gas chromatography-mass spectrometry (GC-MS), and the chemical structures of the anisaldehyde products were confirmed by comparison with a standard spectral library. Quantitative analysis was performed using gas chromatography, and a calibration curve was established using standards of the target products. The content of the reaction products was then quantitatively calculated using the external standard method.
[0108] Depend on Figure 1 It can be seen that, compared with the Co3O4 catalyst without oxygen vacancies, the Co3O4 with oxygen vacancies obtained in Example 1 showed a higher substrate conversion rate in the aqueous electrochemical oxidation of methoxytoluene. At the same time, the Faraday efficiency and product selectivity of methoxybenzaldehyde were significantly improved, indicating that the introduction of oxygen vacancies is beneficial to promoting the selective oxidation reaction of methyl aromatics.
[0109] Depend on Figures 2-5 It can be seen that after the introduction of oxygen vacancies, the catalyst still maintains the bulk crystal phase structure of Co3O4, and its crystal structure has not changed significantly. Moreover, the overall catalyst still exhibits a stable nanosheet morphology, indicating that the introduction of oxygen vacancies has not destroyed the main structure and morphological characteristics of the catalyst.
[0110] Depend on Figures 6-7 As can be seen, compared with the Co3O4 prepared in Comparative Example 1, the oxygen-vacancy-containing Co3O4 obtained in Example 1 exhibits more obvious lattice distortion and defect characteristics in high-resolution structural characterization, indicating that there are a large number of structural defects in the catalyst lattice, further proving the successful introduction of oxygen vacancies.
[0111] Depend on Figures 8-9 It can be seen that the oxygen-containing vacancy Co3O4 obtained in Example 1 showed a significantly enhanced oxygen vacancy characteristic signal in the electron paramagnetic resonance (EPR) test, while the signal in the sample of Comparative Example 1 was significantly weaker, which further confirms the existence of oxygen vacancies in the catalyst of Example 1.
[0112] Depend on Figures 10-11 It can be seen that the oxygen-vacancy-containing Co3O4 catalyst obtained in Example 1 exhibits a higher proportion of defect oxygen or vacancy oxygen components in the XPS O 1s spectrum. Compared with the sample of Comparative Example 1, its vacancy oxygen peak area is significantly increased, indicating that oxygen vacancies have a high abundance on the catalyst surface.
[0113] The above content is only a specific implementation example of the present invention, and not all application examples of the present invention. All schemes that follow the technical concept of the present invention or make modifications based on the technical concept of the present invention are within the protection scope of the claims of the present invention.
Claims
1. A method for the selective oxidation of benzyl CH bonds in an oxygen vacancy-induced aqueous system to prepare anisaldehyde, characterized in that, In the electrochemical reaction system, a transition metal oxide containing oxygen vacancies is used as the anode. Under the action of an applied electric field, methyl aromatic compounds undergo an electrochemical oxidation reaction to generate anisaldehyde.
2. The method for preparing anisaldehyde by selective oxidation of benzyl CH bonds in an aqueous system induced by oxygen vacancy, as described in claim 1, is characterized in that... Includes the following steps: S1. Construct an electrochemical reaction system, wherein the electrochemical reaction system includes an anode, a cathode, and an electrolyte; A cobalt oxide catalyst is supported on the anode; S2. Introduce a methyl aromatic compound containing a benzyl CH bond into the electrochemical reaction system; S3. An electrolytic reaction is carried out under an external tank pressure to cause the methyl aromatic compound to undergo a selective oxidation reaction at the anode, generating the corresponding anisaldehyde product.
3. The method for preparing anisaldehyde by selective oxidation of benzyl CH bonds in an aqueous system induced by oxygen vacancy, as described in claim 2, is characterized in that... In step S1, the cobalt oxide catalyst is cobalt tetroxide containing oxygen vacancies.
4. The method for preparing anisaldehyde by selective oxidation of benzyl CH bonds induced by oxygen vacancy in an aqueous system according to claim 3, characterized in that, The oxygen-vacant cobalt tetroxide is prepared by the following method: First, a cobalt hydroxide precursor is electrodeposited on the surface of a conductive substrate, and then calcined under an inert atmosphere at a temperature of 300-600 °C for 1-4 h.
5. The method for preparing anisaldehyde by oxygen vacancy-induced aqueous electrocatalytic selective oxidation of benzyl CH bonds according to claim 2 or 3, characterized in that, The cobalt oxide catalyst is supported on a conductive substrate, which is either a titanium mesh or a titanium foil, wherein the titanium mesh is 100-600 mesh.
6. The method for preparing anisaldehyde by selective oxidation of benzyl CH bonds in an aqueous system induced by oxygen vacancy according to claim 2, characterized in that, In step S1, the electrochemical reaction is carried out in a dual-electrode system without a diaphragm or with an ion exchange membrane.
7. The method for preparing anisaldehyde by selective oxidation of benzyl CH bonds in an aqueous system induced by oxygen vacancy, as described in claim 2, is characterized in that... In step S1, the electrolyte is an electrolyte system mainly composed of water, and may optionally contain a small amount of organic co-solvent, which is one or more of acetonitrile, methanol or acetic acid.
8. The method for preparing anisaldehyde by oxygen vacancy-induced aqueous electrocatalytic selective oxidation of benzyl CH bonds according to claim 1 or 2, characterized in that, The methyl aromatic compound is p-methoxytoluene and its substituted derivatives; wherein the substituent is halogen, alkyl, alkoxy, nitro or a combination thereof.
9. The method for preparing anisaldehyde by selective oxidation of benzyl CH bonds induced by oxygen vacancy in an aqueous system according to claim 2, characterized in that, In step S3, the electrolysis reaction is carried out under normal temperature and pressure conditions.
10. The method for preparing anisaldehyde by oxygen vacancy-induced aqueous electrocatalytic selective oxidation of benzyl CH bonds according to claim 2, characterized in that, In step S3, the applied tank voltage is a potential range that can drive the selective oxidation of methyl aromatic compounds and inhibit the oxygen evolution reaction, and the applied tank voltage is 2.5~3.0 V.